Development of Physics Summary Book as a Smartphone-Based Application and Its Effect on Elasticity Learning Achievement - Ahmad Fahrudin (Kasuari: Physics Education Journal (KPEJ), 2018)
The purpose of this study is to determine the effect of the use of learning media book summarizationof physics-based smartphone applications for the achievement of learning elasticity in class XI SMA N 2Lubuklinggau. This research uses two methods of development method (research and development) andquasi-experimental method (quasi-experimental design). Development method using ADDIE developmenton analysis, design, development, implementation, and evaluation. The place of study was conducted in SMAN 2 Kota Lubuklinggau with a sample of 64 students, divided into two experimental classes and controlclass. The objective test was used for data collection in this study. The test is given twice before treatmentand after treatment. The analysis test used parametric statistic with a t-test. The result of the research showsthat there is an increase of learning achievement in the experimental class that shows the minimumcompleteness criteria (KKM) which reaches the learning completeness 93,75% and the learningcompleteness improvement is 75,00% from the pretest value of 18,75%.